2010
DOI: 10.1089/jmf.2008.0311
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic and Anti-Inflammatory Effects of Aqueous Extract of Zea mays Husk in Male Wistar Rats

Abstract: The analgesic and anti-inflammatory activities of Zea mays husk extract (25, 50, 100, and 200 mg/kg of body weight) were investigated in rats. The hot plate and formalin-induced paw licking models were used to assess analgesic effects of the extract, whereas the carrageenan and cotton pellet models were used for the evaluation of anti-inflammatory activity. The extract at 25, 50, 100, and 200 mg/kg body weight significantly (P < .05) reduced pain stimuli and inflammatory activity when compared with the control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…; i.p. for 21 days); 10 Group III (BTE dose of 2.5 g tea leaf/dl of water that is 2.5% of aqueous BTE also for 21 days orally) and Group IV (both indomethacin and BTE simultaneously for 21 days). All the animals were sacrificed at the end of the last dose after an overnight fast.…”
mentioning
confidence: 99%
“…; i.p. for 21 days); 10 Group III (BTE dose of 2.5 g tea leaf/dl of water that is 2.5% of aqueous BTE also for 21 days orally) and Group IV (both indomethacin and BTE simultaneously for 21 days). All the animals were sacrificed at the end of the last dose after an overnight fast.…”
mentioning
confidence: 99%
“…Consumption of Zea mays husk and soy-containing diets suppressed pain in rats up to a significant level. [33,34] These results provide scientific validation for the use of Zea mays husk and Cucurbita maxima seeds for treating pain and inflammatory conditions in Nigerian folk medicine and Brazil, respectively. [34] DPP-III Inhibitory Peptides in Chicken and Bovine Proteins…”
Section: Dpp-iii Inhibitory Peptides In Plant Proteinsmentioning
confidence: 67%
“…Previously, tannins and saponins isolated from medicinal plants exhibited analgesic and anti-inflammatory activities (Thomas et al, 1985;Owoyele et al, 2010;Choi et al, 2005). We thus suggested that the tannins and saponins present in C. vogelii extract were responsible for its analgesic and anti-inflammatory activities.…”
Section: Discussionmentioning
confidence: 92%